ORGANIZATION, PEOPLE'S INSTITUTION AND HUMAN RESOURCES DEVELOPMENT FOR WATERSHED MANAGEMENT - Sharma, J.S. (Journal of Soil and Water Conservation, 2022)
A significant policy decision has been taken by the Govt. of India to endeavor rural development through watershed management strategies during the LV Plan. Food security, productivity rural employment generation, resource conservation and environmental protection are expected to be realized through partnership with local communities. Seventy third Amendment in the Panchayati Raj Act Solemnizes empowerment of the village level institutions for ensuring sustainability and replicability of the resources conservation for meeting livelihood gathering for the present as well as future generations. The guidelines of Ministry of Rural Areas and Employment also envisage greater role of the non- constitutional voluntary bodies and Self Help Groups of like-minded stakeholders. Gender neutrality, equity, emphasis on landless/weaker section/disadvantage persons, productive employment generation, sustainabili4, of the natural resources and realization of environmental externalities are the other paradigms of the development strategies of the Department of Wastelands Development. Capacity building through sensitization of politicians, decision makers, bureaucrats and higher level management is being called upon to make watershed development programme peoples' movement. New paradigms of stakeholders participation, change in attitude/behavior of service providers (Govt. functionaries), greater emphasis on social contents, resolution of conflicts and harmonization of new technologies with the indigenous technical knowledge are the key contents of the training curriculum for meeting the new challenges of watershed development. Institutionalized management of common property resources by devising instrumentalities to take care of resource ownership, sharing of benefits, goods/ services, accountability as well as responsibilities is being integrated in the overall strategies of wasteland development. The current paradigm also enshrines simultaneously joint management of natural resources like land, water, vegetation, livestock, biodiversity and human resources.